Peer Review: A Strategy to Improve Students’ Academic Essay Writings - Polisda, Yen (ENGLISH FRANCA : Academic Journal of English Language and Education, 2017)
The purpose of this article is to describe the importance of peer review on students’ argumentative essay due to problems faced by students and teachers in producing students’ good argumentative essay. Students have problems in making use of the feedback given by teachers. Like students, teachers have problems in giving feedback due the large class and time constraint. The research hypothesis was tested by applying t-test. From the calculation of t-test, tobserved yielded 2.94. The total case degree of freedom was 55 ((27-1) + (30-1)). Ttable at the .05p level and 60 degree of freedom (the closest df) results in a figure of 2.00. This calculation reveals that t-observed could exceed the ttable. It means that the research hypothesis was statistically accepted, and null hypothesis was rejected. This means that the students treated by peer review had higher scores than those treated by teacher review on argumentative essay. Therefore, peer review gives better effect on students’ argumentative essay than the teacher review. Keywords: peer review, argumentative essay writing.